(untitled) (Journal of Accessibility and Design for All, 2015)
People with disabilities are frequently mentioned as beneficiaries of participatory approaches during the research and development of technology, since their special needs and preferences can be unveiled and channeled through participatory techniques. However, there are some challenges affecting their involvement and sustained participation in large-scale R&D technology projects. This paper discusses some strategies to overcome these potential barriers, based on the experience of the authors in two large-scale technology projects funded by the European Commission: AEGIS and CLOUD4all.